Potential water requirements of increased ethanol fuel in the USA - Liu, Xiaowei (Vivian); Hoekman, S. Kent; Broch, Amber (Energy, sustainability and society, 2017)
Background To mitigate climate impacts associated with energy consumption, renewable fuel policies have been established in the USA that encourage production and use of corn ethanol. Current fuel usage of corn ethanol is approximately 15 billion gallons/year (57 billion liters/year), with nearly all of this in the form of E10 (10% blend in gasoline). There is now interest in increasing fuel ethanol usage to achieve nationwide levels of E20 or greater. Due to lack of capacity and poor economics, cellulosic ethanol cannot contribute significantly to increased fuel ethanol production in the near term. Thus, rapid growth of fuel ethanol usage implies expansion of corn ethanol beyond current levels. The objective of this study was to assess the potential water requirements of expanding corn ethanol to provide for nationwide E20 fuel by 2025. Methods A simple modeling approach was used to assess the water requirements for producing 12.5 billion gallons (47.3 billion liters) corn ethanol in the baseline year of 2013 and 24.3 billion gallons (92.0 billion liters) in three future year scenarios of 2025. Irrigation water and process water were considered but not natural rainfall. Baseline inputs regarding corn acreage, crop yields, and irrigation patterns were obtained from the USDA’s National Agricultural Statistics Service (NASS) for each of the 29 corn-producing states in the USA. The three future year scenarios differed in how the required expansion of corn cropping was allocated across the states, thereby resulting in different irrigation patterns. Results As a consequence of differing irrigation requirements, the water intensity of corn ethanol (L water/L ethanol) varied by approximately two orders of magnitude over the 29 corn-producing states. In the 2013 baseline, the water intensity of corn ethanol in Iowa (with 1% irrigated corn acreage) was 5.5 L/L, while that in neighboring Nebraska (with 56% irrigated corn acreage) was 427 L/L. All three future year scenarios result in substantial increases in total volumetric water requirements—from 62 to 161% compared to the 2013 baseline. Conclusions Increasing ethanol blend fuels from E10 to E20 in the near future will require significant expansion of corn cropping in the USA, which will increase irrigation demands. The amount of increased water usage will depend upon the geographic distribution of the cropping expansion. Expansion into already water-stressed areas will exacerbate existing water concerns.